Kemitraan Masyarakat Berbasis Potensi Lokal dengan Model Pendampingan Kelompok Petani untuk Produksi Virgin Coconut Oil (VCO) di Desa Baumata Kupang NTT - Muntasir, Muntasir; Tadeus Andreas Lada Regaletha; Yoseph Kenjam; Sri Prilmayanti Awaluddin; Nadra Aga Iryani (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
This community partnership with target partners can produce VCO products that are fast, easy, simple, have good sanitation, and have quality production, and can be marketed as family or group businesses to increase family income and provide economic value for coconut products. The Assistance Model that is carried out consists of a. Fieldwork team planning; b. Community group discussions; c. Priority Problems handled from the results of group discussions; d. Preparation of Tools and Materials for Intervention; e. Implementation of activity interventions; f. Formative Monitoring and Evaluation of group activities; g. Activity assistance; h. Final Discussion and Final Product Evaluation. The results of this activity indicate that the community members who take part in this activity have the motivation to increase their knowledge and skills in producing VCO which is supported by the evaluation results showing a good assessment from the initial presence to the production of VCO. The Community Partnership Program (PKM) which is aimed at community members in the Baumata village area, Taebenu sub-district, Kupang Regency, NTT, provides a new opportunity to learn and gain understanding and knowledge for the community about selecting coconut materials for VCO production and VCO processing in a simple way with the implementation usable technology. Community members who are in the Baumata village area, Taebenu sub-district, Kupang Regency, and NTT as PKM program partners have additional knowledge in innovating coconut products into processed products with higher economic value. Also, an understanding of simple, easy and hygienic processing methods was obtained from the implementing team